The art of suffering: Postcolonial (Mis)Apprehensions of Nigerian art - Casey, Conerly (Suffering, Art and Aesthetics, 2014)
(Mis)apprehensions of African arts, and their relegation to distant temporal, spatial, and relational realms, are part of violent structures of power that continue to diminish our understanding of others. European and American representations of African arts and aesthetics, embedded in what James Clifford (1988, 225) refers to as the “art-culture” system, tend to devalue them as “primitive,” signs of stagnant, traditional, and unchanging culture, or to value “authentic” forms, typically precolonial art, assumed to hold ritual power.1 With Europeans and Americans, the primary buyers of “authentic” African art, this double bind leaves contemporary African artists unable to sell their work in global art markets, their creativity sidelined to “fake” antiques, or to “copy” Western music, in mimetic processes that entangle African and European artists and consumers. Within the past two decades, however, the global marketing of African art and aesthetics appears to have morphed; European and American consumers continue to assume transcultural, cosmopolitan creativity the purview of Western artists and non-Western cosmopolitanism a sign of “inauthentic” cultural expression, but this dynamic fosters divergent trends—one, a corporate, commoditized branding of “ethnicity” and corporate authentications of ethnic arts (Comaroff and Comaroff 2009), and two, the burgeoning of African and African diasporic markets in which cosmopolitan creolization is a shared aesthetic of postcolonial experience (Hannerz 1997; Larkin 2008